EXPANSION OF THE CONCEPT OF "TECHNOLOGY" - Онопрієнко, М. В. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The variation in the content of the concept of "technology" in connection with problems of transition to a knowledge-society.